Deployment of Concept Design and Fabrication for Flood Rescue Boat Ladder - Mohamad Yusof, Muhammad Nur Iman; Mustafa El Bakri, Helmy (Progress in Engineering Application and Technology, 2025)
Flood disasters in Malaysia frequently challenge rescue teams during the extraction of victims, especially during boarding operations. This project presents the design and development of a flood rescue boat ladder aimed at enhancing safety and efficiency in flood emergencies. A survey conducted with the Fire and Rescue Department (JBPM) Pagoh provided key insights for the design requirements. Several design concepts were generated and evaluated using morphological analysis and the Pugh Controlled Convergence (PuCC) method. A  scaled down prototype of the top rated design concept was developed using 3D printing with Polylactic Acid (PLA) material. The final design incorporated features for multifunctional use as a ladder, ramp, or bridge, addressing critical concerns such as portability, quick deployment, and user safety.